Atividade larvicida da Copaifera langsdorffii (Leguminosae), evidenciada pelas alterações morfohistológicas em Aedes aegypti (Diptera, Culicidae) - Santos, Daniela Braz dos (2015)
The main transmitter species of serotypes of the dengue virus is Aedes aegypti, the most competent mosquitoes and more adapted to urban and man-made environment. The control measures of this disease are still mainly on the vector. Recently, several studies have shown the use of botanical origin of substances with potential insecticide in control of Ae. aegypti, alternatively opposite resistance to conventional insecticides. The efficacy oleoresin of C. langsdorffii the control of Ae. aegypti demonstrated in field work, signals the promising possibility of this botanical compound to control this vector requiring studies to clarify the mechanism of action. Thus, it is proposed to establish the mechanism of death process in the third stage larvae of Ae. aegypti through morfohistologic studies. The larvae of Ae. aegypti were subjected to oil-resin solutions and hexane fraction C. langsdorffii in concentrations of 70 ppm and 80 ppm, respectively. Subsequently collected in time intervals of 6h, 12h and 24h. They were fixed in 4% paraformaldhyde in 0.1 M sodium phosphate buffer pH 7.2, embedded in resin, mounted, stained with hematoxylin-eosin and analyzed by light microscopy. The oil-resin and hexane fraction C. langsdorffii, caused the death of the larvae by the destruction of the posterior cells of the midgut region through cytoplasmatic vacuolation, apical cytoplasmic vesicle formation, lip brush degeneration, increased cellular volume and fold in peritrophic matrix. The changes described in this paper demonstrate how bioactive compounds can trigger cell degeneration and accelerate cell disruption.